The Real Effects of GDP Manipulation on Corporate Innovation: Evidence From China - Deng, Yuemeng; Fang, Fang; Širáňová, Lenka; Zhang, Jie; Cao, Xin (Faculty of Management and Economics of Tomas Bata University in Zlín, 2024)
Corporate innovation is fundamental to the sustainable competitiveness of any economy. This paper examines whether and how local government-level macroeconomic growth pressure induced by gross domestic product (GDP) manipulation in China affects corporate innovation. Using calibrated satellite night light data to construct the GDP manipulation index, we find that GDP manipulation reduces local firms' ' R&D expenditure in the year ahead. The result holds up through robustness tests using different measures of GDP manipulation and corporate innovation. Additionally, we employ an instrumental variable approach to address endogeneity issues and enhance the strength of the causal inference. Furthermore, we find that the effect of GDP manipulation on local corporate innovation is stronger in regions with higher government intervention and where local governments control greater resources. Moreover, this finding is more prominent when local governors face intensified economic growth pressure or promotion incentives. This paper provides evidence that the Chinese government's ' s incentive to boost GDP growth negatively affects corporate innovation. Our findings offer valuable insights for policymakers aiming to stimulate economic growth and enhance competitiveness within their jurisdiction. By implication, it is necessary to form a financial and administrative system that effectively promotes industrial innovation and facilitates the transformation of the economic growth model into one driven by technology and innovation to gain a reasonable competitive advantage both within China and internationally. Future research may explore the evolving dynamics of GDP manipulation's ' s impact on other microeconomic behaviors, with particular focus on how it hinders competitiveness across industries and regions.

Corporate innovation is fundamental to the sustainable competitiveness of any economy. This paper examines whether and how local government-level macroeconomic growth pressure induced by gross domestic product (GDP) manipulation in China affects corporate innovation. Using calibrated satellite night light data to construct the GDP manipulation index, we find that GDP manipulation reduces local firms' ' R&D expenditure in the year ahead. The result holds up through robustness tests using different measures of GDP manipulation and corporate innovation. Additionally, we employ an instrumental variable approach to address endogeneity issues and enhance the strength of the causal inference. Furthermore, we find that the effect of GDP manipulation on local corporate innovation is stronger in regions with higher government intervention and where local governments control greater resources. Moreover, this finding is more prominent when local governors face intensified economic growth pressure or promotion incentives. This paper provides evidence that the Chinese government's ' s incentive to boost GDP growth negatively affects corporate innovation. Our findings offer valuable insights for policymakers aiming to stimulate economic growth and enhance competitiveness within their jurisdiction. By implication, it is necessary to form a financial and administrative system that effectively promotes industrial innovation and facilitates the transformation of the economic growth model into one driven by technology and innovation to gain a reasonable competitive advantage both within China and internationally. Future research may explore the evolving dynamics of GDP manipulation's ' s impact on other microeconomic behaviors, with particular focus on how it hinders competitiveness across industries and regions.
The Real Effects of GDP Manipulation on Corporate Innovation: Evidence From China
Keywords: GDP manipulation; Corporate innovation; Political promotion pressure; China; GDP manipulation; Corporate innovation; Political promotion pressure; China